Potential role of dietary ?-3 essential fatty acids on some oxidant/antioxidant parameters in rats' corpus striatum - Sarsilmaz, M; Songur, A; Özyurt, H; Kus, I; Özen, OA; Özyurt, B; Akyol, Ö (Elsevier Sci Ltd, 2003)
Omega-3 (omega-3) is an essential fatty acid (EFA) found in large amounts in fish oil. It contains eicosapentaenoic acid and docosahexaenoic acid (DHA). DHA is one of the building structures of membrane phospholipids of brain and necessary for continuity of neuronal functions. Evidences support the hypothesis that schizophrenia may be the result of increased reactive oxygen species mediated neuronal injury. Recent reports also suggest the protective effect of omega-3 EFA against neuropsychiatric disorders including schizophrenia. This study proposed to assess the changes in antioxidant enzyme and oxidant parameters in the corpus striatum (CS) of rats fed with omega-3 EFA diet (0.4 g/kg/day) for 30 days. Eight control rats and nine rats fed with omega-3 were decapitated under ether anesthesia, and CS was removed immediately. Thiobarbituric acid-reactive substances (TBARS) and nitric oxide (NO) levels as well as total superoxide dismutase (t-SOD) and xanthine oxidase (XO) enzyme activities in the CS were measured. Rats treated with omega-3 EFA had significantly lower values of TBARS (P < 0.001), NO (P < 0.002) and XO (P < 0.005) whereas higher values of t-SOD enzyme activity (P < 0.002) than the control rats. These results indicate that omega-3 EFA rich fish oil diet reduces some oxidant parameters in CS. This may be revealed by means of reduced CS TBARS levels as an end product of lipid peroxidation of membranes in treated rats. Additionally, reduced XO activity and NO levels may support this notion. On the other hand, although the mechanism is not clear, omega-3 EFA may indirectly enhance the activity of antioxidant enzyme t-SOD. Taken together, this preliminary animal study provides strong support for a therapeutic effect of omega-3 EFA supplemented to classical neuroleptic regimen in the treatment of schizophrenic symptoms and tardive dyskinesia. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: omega-3 essential fatty acids; corpus striatum; lipid peroxidation; xanthine oxidase; superoxide dismutase; nitric oxide